2010
DOI: 10.3354/meps08647
|View full text |Cite
|
Sign up to set email alerts
|

Increased irradiance reduces food quality of sea ice algae

Abstract: The accelerating decrease of Arctic sea ice substantially changes the growth conditions for primary producers, particularly with respect to light. This affects the biochemical composition of sea ice algae, which are an essential high-quality food source for herbivores early in the season. Their high nutritional value is related to their content of polyunsaturated fatty acids (PUFAs), which play an important role for successful maturation, egg production, hatching and nauplii development in grazers. We followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
92
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 62 publications
16
92
1
Order By: Relevance
“…The C:N ratios reported for this area can all be broadly classified as marine, and are similar to previously reported values (Feder et al, 1994). C:N ratios above 12 have been reported for sea ice algae Leu et al, 2010), and also for water column POM in the Northeast Water polynya (Bauerfeind et al, 1997); the C:N ratios we report are lower than this. Consequently, we suggest that sites with higher C:N ratios could reflect contributions from low-quality, N-poor algal matter rather than high C:N terrestrial debris.…”
Section: Discussionsupporting
confidence: 87%
“…The C:N ratios reported for this area can all be broadly classified as marine, and are similar to previously reported values (Feder et al, 1994). C:N ratios above 12 have been reported for sea ice algae Leu et al, 2010), and also for water column POM in the Northeast Water polynya (Bauerfeind et al, 1997); the C:N ratios we report are lower than this. Consequently, we suggest that sites with higher C:N ratios could reflect contributions from low-quality, N-poor algal matter rather than high C:N terrestrial debris.…”
Section: Discussionsupporting
confidence: 87%
“…This was manifested in significant differences between the algal cells exposed at 8 m compared to 0.5-m depth, together with a lack of significant differences between UVR and PAR treatments at the same depth. The physiologically important polyunsaturated fatty acids were reduced in all species compared to their start conditions, and in two of three species, we found higher values at 8 m than at 0.5 m. This is in line with previous studies about the detrimental effect of high-PAR irradiances on algal PUFAs (Leu et al 2006b, c;2010). Leu et al (2006c) found rapid changes in the biochemical composition of another Arctic diatom culture Thalassiosira antarctica var.…”
Section: Discussionsupporting
confidence: 81%
“…Low temperatures and ice cover (i.e. low light) have been proposed to limit the distribution of G. vermiculophylla in the Baltic Sea (Nyberg et al, 2009) but in the present experiment, we found positive growth rates at conditions that are relatively similar to those found under ice (1 µmol photons m -2 s -1 and 5°C: Leu et al, 2010;Smethie et al, 2011). Our results are consistent with the findings of Yokoya et al (1999, see Table 5), who also found positive growth rates at a temperature of 5°C in culture experiments.…”
Section: Discussionsupporting
confidence: 47%